Color Centers Formation in Lithium Fluoride Nanocubes Doped with Different Elements. (18th December 2013) - Salah, Numan; Babkair, Saeed S.; Azam, Ameer
Abstract : Nanocrystalline cubes of pure and doped LiF material were fabricated. They were doped with Cu, Ag, Dy, Tb, and Eu and studied for their PL properties. Shape of the obtained nanocubes was found to be modified by introducing dopants into the host of LiF. The crystallinity was also decreased by increasing the concentration of these dopants (i.e., Eu and Tb). These impurities could induce exothermic peaks at around 250°C in the measured DSC curves. Moreover, incorporating such impurities into the host of LiF was found to enhance intensity of the broad band at 370–550 nm that was observed in the pure one. Extra sharp emissions were also observed in Eu and Tb doped samples. These results showed that the active color centers created in pure LiF nanocubes can be enriched/enhanced by these impurities, mainly Eu and Tb. This implies that these nanocubes might be useful in the development of optical devices and advanced color center laser.